The Effect of Shareholder-Level Dividend Taxes on Stock Prices: Evidence from the Revenue Reconciliation Act of 1993 - Ayers, Benjamin C.; Cloyd, C. Bryan; Robinson, John R. (The Accounting Review, 2002)
We investigate the effect of an increase in the individual (shareholder-level) income tax rate on share values. We regress cumulative daily abnormal stock returns surrounding the passage of the Revenue Reconciliation Act of 1993 on firm dividend yield, tax status of the investor as represented by level of institutional ownership, the interaction of these two variables, and control variables. Consistent with our expectations, we find that (1) the higher the firm's dividend yield, the more negative the firm's stock price reaction to the increase in the individual income tax rate (i.e., the dividend tax rate) enacted in the Revenue Reconciliation Act of 1993, and (2) institutional holdings mitigate this negative reaction. Our results suggest that both the dividend policy of the firm and the tax status of the marginal investor influence the extent to which dividend taxes are reflected in share values. Our evidence is consistent with the traditional view that firm dividend policy influences the extent to which tax rate changes affect share values.